Textile from the Crannog: Analyses and weave experiment of a 2/1 twill weave from Oakbank, Scotland, 400 BCE - Harris, Susanna; Houston, Frances; Oliver, Jason (Archaeological Textiles Review, 2022)
Oakbank Crannog on Loch Tay, Scotland, was built and occupied in the later centuries of the first millennium BCE. Starting in the 1980s and lasting several decades, underwater excavations revealed a variety of organic finds, including a piece of 2/1 twill weave textile preserved in its organic state. The textile appears to be the earliest preserved twill weave textile in Scotland, dating to 400 BCE. It was first studied in the 1990s, and recently as part of a project by the Scottish Crannog Centre (United Kingdom). In the current study, it was analysed to gain new results including a radiocarbon date from the textile, measurements for the characterisation of early fleece through wool quality analysis and updated contextual research. A reconstruction of the textile at the Scottish Crannog Centre found that the 2/1 twill weave was most readily woven on a two-beam vertical loom, and concluded that it was unlikely to have been woven on a warp-weighed loom. No additional conservation treatment or dye analysis was performed. The Scottish Crannog Centre mission is to care for and make accessible the finds of the Crannog dwellers for the benefit and education of all. The textile project involves academics, museum personnel, weavers, crafters and woodworkers, and will be a catalyst for learning and experimentation.